Vlijamie sokratitel'nych i relaksacionnych charakteristik myscc na rost kvalifikacii sportsmenov - Vysocin, Ju. V.; Denisenko, Ju. P.; Cuev, V. A.; Gordeev, J. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was to reveal the factors, influencing the growth of sports qualification in different kinds of sports activity. The examination was carried out by the method of computer polymiography which is based on the synchronous graphic registration of the bioelectric activity and efforts of the researched muscles at their tension and relaxation in the isometric mode. The method allows estimating not only contractile and relaxation characteristics of muscles, but also the functional condition of the central nervous system. More than 1000 athletes of different specializations and various qualifications have taken part in the research. The long-term researches have shown not only the direct dependence of the whole complex of sports important qualities, but also the much greater, in comparison with the contractile characteristics contribution of the speed of relaxation to the progress of sports results.